2007
DOI: 10.3892/or.17.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Functional advantage of NPC-related V-val subtype of Epstein-Barr virus nuclear antigen 1 compared with prototype in epithelial cell line

Abstract: Epstein-Barr virus (EBV) is closely associated with nasopharyngeal carcinoma (NPC) and the viral nuclear antigen 1 (EBNA1) plays a crucial role in viral latency. Three EBNA1 subtypes, P-ala, V-thr and V-val have been detected from healthy carriers in Guangzhou area. A close relation of V-val EBNA1 with NPC was suggested by its preference to infect NPC cells. We therefore investigated the functional difference among these three EBNA1 subtypes in human epithelial cell line. The three coding sequences of the EBNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It is known that NPC, EBVaGC and nasal NK/T-cell lymphoma are more prevalent in Asia than in other part of the world [44], thus, it is likely that V-val subtype might be more aggressive than other subtypes. Recently, Mai et al [45] and Do et al [46] demonstated that V-val subtype had functional advantage and higher transcriptional activity than P-ala subtype (the B95.8 prototype). As compared with the prototype P-ala, V-val subtype showed 7 amino acid substitutions (codons 439, 487, 499, 502, 524, 528 and 533) with respect to the carboxyl-terminus of EBNA1.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that NPC, EBVaGC and nasal NK/T-cell lymphoma are more prevalent in Asia than in other part of the world [44], thus, it is likely that V-val subtype might be more aggressive than other subtypes. Recently, Mai et al [45] and Do et al [46] demonstated that V-val subtype had functional advantage and higher transcriptional activity than P-ala subtype (the B95.8 prototype). As compared with the prototype P-ala, V-val subtype showed 7 amino acid substitutions (codons 439, 487, 499, 502, 524, 528 and 533) with respect to the carboxyl-terminus of EBNA1.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses of various EBV strains indicate that T585 is among the EBNA1 polymorphisms found frequently in both NPC tumors and Burkitt's lymphoma (35)(36)(37)(38)(39)(40)(41). Recently, our laboratory found that an NPC variant of EBNA1 containing 8 amino acid polymorphisms different from the prototypical B95-8 strain, including a T585I substitution, was defective in replication and maintenance of the viral episome (41).…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of EBV in the pathogenesis of EBV-associated malignancies remains to be determined. The fact that EBV infection is ubiquitous around the world yet the incidence of EBV-associated malignancies differs geographically raises the possibility that certain EBV strains may contribute to the development of specific EBV-associated malignancies [7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%